Emergency presentation and immediate outcome of children with autoimmune hemolytic anemia - Muthukrishnan, Lakshmi; Raman, Radhika; Rabia, Seyed (Indian Journal of Child Health, 2022)
Aim: This study aims to analyze the clinical spectrum, severity of anemia, challenges in arranging cross matched blood in the emergency department (ED), and treatment outcomes of children with autoimmune hemolytic anemia (AIHA). Methods: Retrospective analysis was conducted in the tertiary care pediatric ED between October 2019 and September 2021. All direct antiglobulin test (DAT)-positive children were included in the study and those DAT negative were excluded from the study. The details regarding clinical condition, laboratory parameters, history of previous transfusion, difficulties related to cross-matching, requirement of steroid, and intensive care management were documented. Results: A total of 29 children were diagnosed to have AIHA. The most common clinical feature at diagnosis was fever (72.4%) followed by pallor (51.7%). Cross-matching was difficult for 9 children (31%) due various incompatibilities. Ten children required intensive care. Secondary causes were identified in 25 cases. Mortality was 10%. Conclusion: Identifying secondary causes of pediatric AIHA are essential and larger data from multiple centers will contribute toward creating the best clinical approach and emergency management of children with AIHA.